"Pous Abraham de Eerste": De Onderzoeker oor Kuyper - Lubbe, J. J. (Hervormde teologiese studies, 1994)
‘Pope Abraham the First’: Kuyper as introduced by De Onderzoeker Towards the end of the previous century, theologians, ministers and interested members of the Dutch Reformed Church became familiar with the name of Neo-Calvinist Abraham Kuyper De Onderzoeker, the theological mouthpiece of the Cape liberal movement between 1860 and 1884, quite unexpectedly was one of the first to take note of this theologian, and in a peculiar sense. This article tries to determine the content and possible influence of that introduction. To be true to the historical context, it is, however, necessary first to understand something of the character of De Onderzoeker.